Influence of Protective Face Coverings on the Speech Recognition of Cochlear Implant Patients. (16th February 2021) - Vos, Teresa G.; Dillon, Margaret T.; Buss, Emily; Rooth, Meredith A.; Bucker, Andrea L.; Dillon, Sarah; Pearson, Adrienne; Quinones, Kristen; Richter, Margaret E.; Roth, Noelle; Young, Allison; Dedmon, Matthew M.
Abstract : Objectives: The objectives were to characterize the effects of wearing face coverings on: 1) acoustic speech cues, and 2) speech recognition of patients with hearing loss who listen with a cochlear implant. Methods: A prospective cohort study was performed in a tertiary referral center between July and September 2020. A female talker recorded sentences in three conditions: no face covering, N95 mask, and N95 mask plus a face shield. Spectral differences were analyzed between speech produced in each condition. The speech recognition in each condition for twenty‐three adult patients with at least 6 months of cochlear implant use was assessed. Results: Spectral analysis demonstrated preferential attenuation of high‐frequency speech information with the N95 mask plus face shield condition compared to the other conditions. Speech recognition did not differ significantly between the uncovered (median 90% [IQR 89%–94%]) and N95 mask conditions (91% [IQR 86%–94%]; P = .253); however, speech recognition was significantly worse in the N95 mask plus face shield condition (64% [IQR 48%–75%]) compared to the uncovered ( P < .001) or N95 mask ( P < .001) conditions. Conclusions: The type and combination of protective face coverings used have differential effects on attenuation of speech information, influencing speech recognition of patients with hearing loss. In the face of the COVID‐19 pandemic, there is a need to protect patients and clinicians from spread of disease while maximizing patient speech recognition. The disruptive effect of wearing a face shield in conjunction with a mask may prompt clinicians to consider alternative eye protection, such as goggles, in appropriate clinical situations. Level of Evidence: 3 Laryngoscope, 131:E2038–E2043, 2021